Evaluasi jenis dan pola penanaman tanaman di median Jalan Ir. Soekarno Kota Saumlaki, Maluku Tenggara Barat - Lerebulan, Merlin F. A.; Asmiwyati, I Gusti Agung Ayu Rai; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020, 2020)
Evaluation of type and planting system at the median road of Ir. SoekarnoMedian strips the City of Saumlaki, Maluku Tenggara Barat. Planting plants in the median strip Ir. Soekarno was dominated by Trembesi trees (Samanea saman) with tree branches that grew beyond the median strip. It was quite dangerous for road users because the Trembesi trees can easily be fallen when exposed to strong winds. Despite its problems, the Trembesi tree had ecological potential benefits such as the highest oxygen-producing and pollutant-absorbing capacity. This study aims to determine and evaluate the types of plants in terms of the physical categories and functions of plants and spacing. This study was located in Ir. Soekarno Road, South Tanimbar District, Town of Saumlaki, Maluku Tenggara Barat Regency. The standard of assesment for median road plant used The Guidelines Regulation of Public Works Minister 2008. Survey method with quantitative descriptive approach was used was this study by taking four samples of the median road segment. The physical assessment results for the four samples varied, those were moderate, good, and very good. The assessment result of functions in each segment had been fulfilled the categories with good and very good criteria, howevere the function needs to be improved. The value of distance assessment for each segment varied, those were good and very good. In order to increase plant distance category, it was necessary to add plants in each segment.